Brand Image, Customer Loyalty And Price To Consumer Purchase Decisions (Study On Customer Cafe & Resto Enzym Signature Palopo City) - Muammar Khaddapi; M. Risa; Nana Adriana (Jurnal Mantik, 2022)
This research was conducted with the aim of knowing and analyzing the influence of brand image, customer loyalty and price variables on consumer purchasing decisions at cafes and restaurants with enzyme signatures in Palopo City. The data in this research are primary data and the data collection technique in this research uses a questionnaire. The number of samples drawn from the population is 95 samples. Multiple linear regression was applied in this study to analyze the data. For data analysis using SPSS 21. The results of this study, simultaneously variable price brand image and customer loyalty affect the variables of consumer purchasing decisions at cafes and restaurants enzyme signature in the city of Palopo. Based on individualvariable brand image, price and customer loyalty have a positive and significant effect on consumer purchasing decisions at cafes and restaurants with enzyme signatures in Palopo City.